The Q and QTc Study (Quinine and QTc Interval Prolongation Study) (Medical Forum Monthly, 2024)
Objective: The objective of this study is to determine the effect of Quinine on QTc interval.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Medicine Department of Saidu Teaching Hospital Saidusharif Swat from 1st October 2015 to 1st October 2016.Materials and Methods: A total of 100 patients both male and female who needed Quinine for febrile illness were included Pretreatment ECG and post treatment ECG (on the last day of Quinine treatment) was recorded. Patients were divided in three groups on the basis of pretreatment ECGGroup I: (50%) pretreatment ECG QTc interval was 361 to 400msec (mean) 380 msec.Group II: (30%) pretreatment QTC interval 401 to 450msec with mean 425.5msec.Group III: (20%) pretreatment QTC interval 451 to 485msec with mean 468msec.Patients were given Quinine according to the protocol and post treatment QTc interval was recorded.Results: Values were analyzed on student T- Test with a P value of 0.006.Conclusion: It is concluded that Quinine increases the QTc interval to a significant level.